Teachers’ Interpersonal Style in Physical Education: Exploring Patterns of Students’ Self-Determined Motivation and Enjoyment of Physical Activity in a Longitudinal Study - Fin, Gracielle; Moreno-Murcia, Juan Antonio; León, Jaime; Baretta, Elisabeth; Nodari Júnior, Rudy José (Frontiers in Psychology, 2019)
This longitudinal study explored patterns of basic psychological needs and self-determined motivation, as well as its association with the teaching style and the physical activity enjoyment in a group of students. The sample consisted of 200 secondary education students (105 girls and 95 boys) aged 11 to 13 years (M = 12.65, SD = .79) at the start of the study. Students were assessed twice in a 22 month-period. Descriptive analyses were conducted between major variables at both time points, and to explore the number and nature of clusters, we relied on latent profile analysis. The statistical analyses showed three different patterns: downwards, stable and upwards, with different outcomes and determinants. The downwards pattern was associated with more negative enjoyment and a controlling style, while the upwards pattern with more positive enjoyment and autonomy support. This study, which was based on a person-centered approach, provided a bigger picture of the interplay between autonomy, competence, relatedness, self-determined motivation, autonomy/control support, and physical activity enjoyment.